Liquidity, trading rules, and electronic trading systems - Harris, Lawrence E.; Saunders, Anthony; Jaffier, Mary.; Salomon Brothers Center for the Study of Financial Institutions; Leonard N. Stern School of Business (New York : Leonard N Stern School of Business, 1990)
This analysis starts with a definition of liquidity. The traders who offer it and the risks and rewards that they face are then identified. The discussion also considers how different trading rules and market structures might attract more liquidity than is currently supplied in American markets. The competitive environment is examined to determine whether new market structures will develop if existing markets do not change. The conclusion provides a summary and a prospective for the exchange industry.
On page 2 of cover: Leonard N. Stern School of Business.
Includes appendices.
rpm 05/09/2016
Ref
Keywords: Stock exchanges -- Data processing; Stocks; Securities; Liquidity (Economics)